2001
DOI: 10.1042/0264-6021:3540115
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of [6R]-5-formyltetrahydrofolate, an unnatural isomer, in humans and Enterococcus hirae, and cytochrome c oxidation of 10-formyltetrahydrofolate to 10-formyldihydrofolate

Abstract: The bio-inactive C-6 isomer, [6R]-5-formyl-tetrahydrofolate (5-HCO-H(4)F), is not found in Nature. An oral dose of 13.5 micromol of [6R]-5-HCO-H(4)F in humans results in the appearance of the naturally occurring [6S]-5-methyl-tetrahydrofolate and relatively large amounts of other bioactive folates in plasma. The removal of the asymmetry at C-6 could account for these results. Two oxidized cytochrome c [cyt c (Fe3+)] molecules oxidize one 10-formyl-tetrahydrofolate (10-HCO-H(4)F) with second-order kinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It is assumed that only the [6 S ] form, which is half the administered dose, is bio‐active. However evidence exists that the [6 R ] racemate of 5‐formyltetrahydrofolate can also be biologically active, although it is not known whether this also applies to the [6 R ] form of 5‐MeTHF [19–21].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that only the [6 S ] form, which is half the administered dose, is bio‐active. However evidence exists that the [6 R ] racemate of 5‐formyltetrahydrofolate can also be biologically active, although it is not known whether this also applies to the [6 R ] form of 5‐MeTHF [19–21].…”
Section: Introductionmentioning
confidence: 99%
“…Since DHF is metabolically active, this process explains the bioactivity of the above unnatural carbon-6 isomers. Recently, Baggott et al (4) reported that (6RS)-10-HCO-THF is converted to 10-HCO-DHF by a rapid nonenzymatic reaction with oxidized cytochrome c, thereby reducing the cytochrome. These findings lead us to hypothesize that the oxidation of 10-HCO-THF to 10-HCO-DHF takes place in mitochondria, that 10-HCO-THF supports mitochondrial respiration, and that cytochrome c is an oxidant.…”
mentioning
confidence: 99%
“…22 Therefore, 10-HCO-H 2 folate cannot be prepared in vitro without being contaminated with oxidation products. 23 Oxidized cytochrome C reacts with 10-HCO-H 4 folate with a second-order rate constant of 1.3 Â 10 4 /mol/L Â s. 10 As cytochrome C concentration is 100-200 mmol/L in the intermembrane space, and mitochondrial folate concentration is 1-5 mmol/L, the pseudo-first-order oxidation rate suggests that 10-HCO-H 4 folate would have a half-life of 1 s or less in the intermembrane space. 10 As the protein porin forms channels in the outer mitochondrial membrane that allow free diffusion of molecules of 10,000 Da or less, 24 10-HCO H 4 folate and its polyglutamates found in the cytoplasm could come in contact with cytochrome C in the intermembrane space and diffuse out to the cytoplasm as 10-HCO-H 2 folate to be utilized by AICAR transformylase.…”
Section: Presence Of 10-formyldihydrofolate In Vivomentioning
confidence: 99%
“…The obligate intermediate in this two-step-oxidation process is 10-HCO-H 2 folate that was in fact tentatively identified in the human bile. 7 The first oxidation of 10-HCO-H 4 folate to 10-HCO-H 2 folate is more rapid than the second oxidation to 10-HCO-folic acid, 6,10 suggesting that 10-HCO-H 2 folate was rapidly formed after the dose of folic acid or 5-HCO-H 4 folate. Labeled 10-HCO-folic acid was also identified in the rat liver, bile and urine after the dose of [ 14 C]- and [ 3 H]-labeled folic acid.…”
Section: Presence Of 10-formyldihydrofolate In Vivomentioning
confidence: 99%
See 1 more Smart Citation